Natural Resource Dependency and Entrepreneurship: Are Nations with High Resource Rents Cursed?. (7th October 2018) - Chambers, Dustin; Munemo, Jonathan
Abstract: Testing the hypothesis that the resource curse promotes rent‐seeking behaviour at the expense of entrepreneurship, we examine the relationship between natural resource rents and new business creation using a panel of 116 countries spanning the period 2001–2012. We find that nations with heavy natural resource extraction exhibit less entrepreneurial activity, but this negative relationship is greatly reduced and even reversed in nations possessing a threshold level of governance quality. Unfortunately, the group of nations exceeding this threshold consists primarily of Organization for Economic Cooperation and Development members. These results support the hypothesis that the resource curse, when left unchecked by weak institutions, promotes rent‐seeking behaviour that harms entrepreneurship. © 2018 John Wiley & Sons, Ltd.